Leptin Receptor Gene Gln223Arg Polymorphism Is Not Associated with Hypertension: A Preliminary Population-Based Cross-Sectional Study - Geórgia das Graças Pena; Andre L. S. Guimarães; Rosângela R. Veloso; Tatiana C. Reis; Crizian S. Gomes; João F. R. Neto; Gustavo Velasquez-Melendez (Cardiology Research and Practice)
Hypertension is responsible for high morbidity and mortality as one of the most important cardiometabolic risk factors. The aim of the study was to investigate whether the Gln223Arg in the leptin receptor (LEPR) influences the prevalence of hypertension. A cross-sectional study was carried out in individuals aged ≥ 18 years. Polymorphism identification was performed using PCR-RFLP analysis. Participants with blood pressure ≥ 140/90 mmHg or medication use were considered hypertensive. Frequencies, means, cross-tabulations, and multivariate models were produced to study differences in hypertension prevalence by genotypes. The study includes 470 participants. The frequency of GG polymorphism variant was 10.43%, 46.81% AG, and 42.77% AA. The distribution of hypertension frequency by LEPR genotypes was the following: AA 43.8%, AG 40.4%, and GG 40.8%; there were no significant differences between groups. Comparative analysis which used multivariate Poisson regression adjusted by many potential confounders (age, sex, schooling, smoking, alcohol intake, obesity, and family history of parental obesity) did not modify this result. In this large sample of population-based study, the association of the LEPR Gln223Arg gene polymorphism with hypertension was not observed.